2016
DOI: 10.1098/rstb.2015.0073
|View full text |Cite
|
Sign up to set email alerts
|

Group bias in cooperative norm enforcement

Abstract: One contribution of 16 to a theme issue 'Understanding self and other: from origins to disorders'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 63 publications
8
70
0
Order By: Relevance
“…For example, Guala and Filippin () found that people altruistically allocated more money towards an ingroup member victim and were more likely to punish an outgroup perpetrator (Guala & Filippin, ). This finding is further supported by previous research which has observed that ingroup members who violate social norms will be less harshly punished than outgroup members due to ingroup favouritism (DeSmet et al, ; Guala & Filippin, ; Guo, Xu, Wu, & Hu, ; McAuliffe & Dunham, ; Wang et al, ). What remains less known, however, is whether the identity of the perpetrator (as an ingroup or outgroup member) moderates or is moderated by other factors (e.g., empathy, perceived injustice) in the dictator game and influences altruistic behaviour choices.…”
Section: Introductionsupporting
confidence: 82%
“…For example, Guala and Filippin () found that people altruistically allocated more money towards an ingroup member victim and were more likely to punish an outgroup perpetrator (Guala & Filippin, ). This finding is further supported by previous research which has observed that ingroup members who violate social norms will be less harshly punished than outgroup members due to ingroup favouritism (DeSmet et al, ; Guala & Filippin, ; Guo, Xu, Wu, & Hu, ; McAuliffe & Dunham, ; Wang et al, ). What remains less known, however, is whether the identity of the perpetrator (as an ingroup or outgroup member) moderates or is moderated by other factors (e.g., empathy, perceived injustice) in the dictator game and influences altruistic behaviour choices.…”
Section: Introductionsupporting
confidence: 82%
“…In the Ultimatum Game, both theories have been supported. A recent review of the literature appraised studies on group bias in norm enforcement and indicated that most findings are more consistent with the Social Identity Theory than the Norms-Focused Theory12.…”
mentioning
confidence: 99%
“…Some authors propose a Norm-Focused Theory, emphasize the functional role of prescriptive norms which help to maintain group cohesion and promote group interest. Accordingly, the violation of such norms will be highly salient and objectionable, violating the central compact of group life12. According to the Social Identity Theory, other researchers propose that an ingroup member’s unfair action will at least partially be compensated by the positive evaluation they gain through group membership1314.…”
mentioning
confidence: 99%
“…McAuliffe & Dunham [26] adopt an intergroup perspective on the relationship between self and other and discuss why children prefer members of their own group. They discuss evidence that both adults and children tend to share more resources with members of their own group and critically evaluate why this is.…”
Section: Origins: the Evolution And Development Of Social Cognitionmentioning
confidence: 99%